Enhancement of P3HT:PCBM Photovoltaic Shells Efficiency Incorporating Core-shell Au@Ag Plasmonic Nanoparticles1. (2016) - Tzounis, L.; Gravalidis, C.; Papamichail, A.; Logothetidis, S.
Abstract: We report on a simple and scalable process for the synthesis of core-shell Au@Ag (Gold core @ Ag shell) bimetallic plasmonic nanoparticles (NPs) with an average size in the range of 40 nm, endowing a remarkable improvement of the power conversion efficiency (PCE) of air processed organic photovoltaics (OPVs) upon being deposited onto the active layer. The beauty of the current work lies on the fact that the spin coated OPV devices; exhibiting a normal architecture consisting of a Glass/ITO (Indium Tin Oxide) anode, a poly-3, 4-ethylenedioxy-thiophene:poly(styrenesulfonic-acid) (PEDOT:PSS) hole transport layer (HTL), a poly(3-hexylthiophene) (P3HT) and methanofullerene derivative (PCBM) bulk heterojunction (BHJ) photoactive blend layer (P3HT:PCBM), a Au@Ag plasmonic NPs layer, a Calcium (Ca) electron transport layer (ETL), and an Aluminium (Al) cathode, were processed in ambient conditions. The plasmonic NP layer, which was deposited onto the active layer after a short period of O2 plasma treatment to enhance the adhesion of the water based NP dispersion (limited time of plasma treatment for 20 sec at a pressure of 1.12 mbar and at 10 Watts power), resulted in a 20.1% enhancement of the PCE compared to reference devices. Namely, the PCE was enhanced from 2.24 to 2.69%. The spin coating parameters for the optimum film morphology, thickness, optical properties, etc of all the OPV layers, as well as the desirable morphology at the nanometer scale of the BHJ have been followed according to previous established protocols. Ultraviolent visible (UV-vis) spectroscopy demonstrated the localised surface plasmon resonance (LSPR) peak of the plasmonic NPs. Scanning and transmission electron microscopy (SEM, TEM) depicted the distribution and the surface coverage of Au@Ag NPs above the active layer as well as their geometry and size, respectively. This study shows for the first time the utilization of plasmonic NPs as a means to improve the PCE of air processed OPVs, which is known to get deteriorated by ambient conditions processing.